Application of 3D Mass Spectrometry Imaging to TKIs. Issue 5 (10th October 2017) - Morosi, Lavinia; Giordano, Silvia; Falcetta, Francesca; Frapolli, Roberta; Licandro, Simonetta A.; Matteo, Cristina; Zucchetti, Massimo; Ubezio, Paolo; Erba, Eugenio; Visentin, Sonja; D'Incalci, Maurizio; Davoli, Enrico
Abstract : Mass spectrometry imaging (MSI) allows visualization of endogenous and exogenous compound in tissue sections based on its molecular mass. The 3D reconstruction by MSI provides a more informative description of the tumor drug distribution compared to the high‐performance liquid chromatography method, highlighting the heterogeneity of intratumor drug concentration. This additional information can be important in understanding chemoresistance to target agents. Here, we present the 3D visualization of the tyrosine kinase inhibitor (TKI), imatinib, in a xenograft model of resistant malignant pleural mesothelioma.